2001
DOI: 10.1002/ijc.1511
|View full text |Cite
|
Sign up to set email alerts
|

Interval cancers in the Norwegian breast cancer screening program: Frequency, characteristics and use of HRT

Abstract: Key words: mammography screening; interval cancer; breast density; HRTAs a result of the mortality reduction found in several randomized controlled clinical trials, 1,2 breast cancer screening programs have been implemented in several western countries. 3 The Norwegian Breast Cancer Screening Program is a population-based program that offers women aged 50 -69 years biannual mammography screening. The program started as a pilot project in 4 counties in 1996, and the results from the first screening round were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 31 publications
(24 reference statements)
5
40
0
1
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] A metaanalysis of population-based programmes showed a 6-fold variation in the level of IC in the first year after mammographic screening. 17 However, several important issues affect the estimation of IC frequency and, consequently, their comparability and interpretation.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] A metaanalysis of population-based programmes showed a 6-fold variation in the level of IC in the first year after mammographic screening. 17 However, several important issues affect the estimation of IC frequency and, consequently, their comparability and interpretation.…”
mentioning
confidence: 99%
“…Wang et al found a significant relationship between ever-use of postmenopausal hormone therapy (HT) and mammographic density, but no information on the type of HT was available. 15 On the basis of the differences in HT formulas described, more knowledge about how different types of HT effect mammographic density could increase the understanding of the etiology of breast cancer.…”
mentioning
confidence: 99%
“…Only few service screening programs have reached performance and sensitivity figures reported from the randomized studies. [6][7][8][9] There has also been variation in the performance between and within screening programs in different countries. [10][11][12] In Finland, mortality impact of the mammography program has been demonstrated earlier.…”
mentioning
confidence: 99%